STRATEGI PEMBELAJARAN MELALUI DARING DAN LURING SELAMA PANDEMI COVID-19 DI SD NEGERI SUGIHAN 03 BENDOSARI - Ayusi Perdana Putri; Rennita Setya Rahhayu; Meidawati Suswandari; Prapti Agustin Rahayu Ningsih (Program Studi PGSD Universitas Flores, 2021)
This study aims to describe the strategy for implementing online and offline learning during the Covid-19 pandemic at SD Negeri Sugihan 03, Bendosari. This research use desciptive qualitative approach. The sampling technique used purposive sampling. The informants in this were teachers and students of grade VI SD Negeri Sugihan 03. The data collection techniques used included interviews, observation, and documentation. Data analysis using data reduction techniques, data presentation and drawing conclusions. The results of this study indicate that the learning implementation strategy during the Covid-19 pandemic includes 1) door-to-door or the teacher visiting each student's house. 2) students come directly to school to take questions. 3) students attend school on alternate schedules during the pandemic.